Performance of Farm Women in Agriculture and Income Generating Activities - Thejaswini C.N; Chandra Shekar v; Narayana Gowda. K (Journal of Agricultural Extension Management, 2025)
It is a well known fact that women’s income in a family is of paramount importance for nutritional, economic and educational upliftment of the family. Since women constitute almost half of the population in India, the burden shared by her for the socio-economic development is of two folds - one on the domestic front and the other on the economic front. However, the employment opportunities in rural areas are low because of the fact that the employment opportunities in rural areas are low because of the fact that the agriculture is of seasonal in nature. As a result of scarce employment opportunities and life supporting activities, women are tend to migrate to other areas seeking for livelihood (Leelamma, 2001)